A zebrafish model of glucocorticoid resistance shows serotonergic modulation of the stress response - Griffiths, Brian; Schoonheim, Peter J.; Ziv, Limor; Voelker, Lisa; Baier, Herwig; Gahtan, Ethan (Frontiers in Behavioral Neuroscience, 2012)
One function of glucocorticoids is to restore homeostasis after an acute stress response by providing negative feedback to stress circuits in the brain. Loss of this negative feedback leads to elevated physiological stress and may contribute to depression, anxiety and post-traumatic stress disorder. We investigated the early, developmental effects of glucocorticoid signaling deficits on stress physiology and related behaviors using a mutant zebrafish, grs357, with non-functional glucocorticoid receptors. These mutants are morphologically inconspicuous and adult-viable. A previous study of adult grs357 mutants showed loss of glucocorticoid-mediated negative feedback and elevated physiological and behavioral stress markers. Already at five days post-fertilization, mutant larvae had elevated whole body cortisol, increased expression of pro-opiomelanocortin (POMC), the precursor of adrenocorticotropic hormone (ACTH), and failed to show normal suppression of stress markers after dexamethasone treatment. Mutant larvae had larger auditory-evoked startle responses compared to wildtype sibling controls (grwt), despite having lower spontaneous activity levels. Fluoxetine (Prozac) treatment in mutants decreased startle responding and increased spontaneous activity, making them behaviorally similar to wildtype. This result mirrors known effects of selective serotonin reuptake inhibitors (SSRIs) in modifying glucocorticoid signaling and alleviating stress disorders in human patients. Our results suggest that larval grs357 zebrafish can be used to study behavioral, physiological and molecular aspects of stress disorders. Most importantly, interactions between glucocorticoid and serotonin signaling appear to be highly conserved among vertebrates, suggesting deep homologies at the neural circuit level and opening up new avenues for research into psychiatric conditions.